Application of the DMAIC methodology in the analysis of the OTIF indicator in a metal mechanical industry - Braga, Raelly Atena de Cerqueira; Pereira, Natália Fernanda Santos; Barbosa, Leandro César Mol; Mapa, Silvia Maria Santana (Brazilian Journal of Production Engineering, 2023)
This study was applied in an industry that produces tubes with high demands in terms of deadlines and compliance with the characteristics of the products. In this context, the OTIF (On Time In Full) indicator is fundamental as a way of evaluating the company's performance and reflecting customer satisfaction regarding deliveries.  Initially, the company did not meet the established target. Thus, the objective was to search the main causes that avoid the achievement of the OTIF goal through the DMAIC methodology, prioritize actions with the help of the GUT / Pareto diagram and propose an action plan to improve results using 5W1H. It was also observed that part of the problems were caused by poor communication between areas, impacting other sectors that did not have access to information, making it necessary to apply adequate knowledge management with registration and sharing with the people impacted. It can be concluded that the chosen tools helped to find the main causes related to non-compliance with the OTIF, defining and prioritizing improvement actions.
Keywords: On Time In Full; Logistic; DMAIC; GUT; 5W1H; Pareto